Time to Block: Early Regional Anesthesia Improves Pain Control in Geriatric Hip Fractures. (20th May 2020) - Garlich, John M.; Pujari, Amit; Debbi, Eytan M.; Yalamanchili, Dheeraj R.; Moak, Zachary B.; Stephenson, Samuel K.; Stephan, Stephen R.; Polakof, Landon S.; Johnson, Christopher R.; Noorzad, Ali S.; Little, Milton T.M.; Moon, Charles N.; et al.
Abstract : Background: Fascia iliaca nerve blocks (FIBs) anesthetize the thigh and provide opioid-sparing analgesia for geriatric patients with hip fracture awaiting a surgical procedure. FIBs are recommended for preoperative pain management; yet, block administration is often delayed for hours after admission, and delays in pain management lead to worse outcomes. Our objective was to determine whether opioid consumption and pain following a hip fracture are affected by the time to block (TTB). We also examined length of stay and opioid-related adverse events. Methods: This prospective cohort study included patients who were ≥60 years of age, presented with a hip fracture, and received a preoperative FIB from March 2017 to December 2017. Individualized care timelines, including the date and time of admission, block placement, and surgical procedure, were created to evaluate the effect that TTB and time to surgery (TTS) had on outcomes. Patterns among TTB, TTS, and morphine milligram equivalents (MME) were investigated using the Spearman rho correlation. For descriptive purposes, we divided patients into 2 groups based on the median TTB. Multivariable regression for preoperative MME and length of stay was performed to assess the effect of TTB. Results: There were 107 patients, with a mean age of 83.3 years, who received a preoperative FIB. The median TTB was 8.5 hours. Seventy-two percent of preoperative MME consumption occurred before block placement (pre-block MME). A longer TTB was most strongly correlated with pre-block MME (rho = 0.54; p < 0.001), and TTS was not correlated. Patients with a faster TTB consumed fewer opioids preoperatively (12.0 compared with 33.1 MME; p = 0.015), had lower visual analog scale scores for pain on postoperative day 1 (2.8 compared with 3.5 points; p = 0.046), and were discharged earlier (4.0 compared with 5.5 days; p = 0.039). There were no differences in preoperative pain scores, postoperative opioid consumption, delirium, or opioid-related adverse events. Multivariate regression showed that every hour of delay in TTB was associated with a 2.8% increase in preoperative MME and a 1.0% increase in the length of stay. Conclusions: Faster TTB in geriatric patients with hip fracture may reduce opioid use, pain, and length of stay. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.